Identifying factors associated with substantially reduced adult height in patients with juvenile idiopathic arthritis: a retrospective cohort study - Hsin-Yu Chen; Ya-Chiao Hu; Yao-Hsu Yang; Bor-Luen Chiang (BMC, 2024)
Abstract Background Juvenile idiopathic arthritis (JIA), an autoimmune disease affecting children or adolescents and causing joint or systemic symptoms, reportedly has a negative effect on the patients' body height. This study aimed to identify factors attributable to substantially reduced adult height (SRAH) in JIA patients. Methods This single-center retrospective cohort study included patients from 2009 to 2019 in Taiwan. We collected JIA patients aged > 18 years at enrollment with a definite diagnosis and undergoing regular outpatient clinic follow-up or disease remission. Target height difference (THD), defined by adult height minus mid-parental height, was calculated for each patient. The calculation results yielded two groups, of which positive THD was defined as the optimal height (OH group) and those with THD below two standardized deviations as the SRAH group. Descriptive statistics and logistic regression analysis were used to analyze the data. Results Of 92 JIA patients, 57 and 12 were in the OH and the SRAH groups. Earlier disease onset, especially before the six-year-old, was noted in the SRAH group (p = 0.026). The distribution of JIA subtypes differed significantly between the two groups (p < 0.001); enthesis-related arthritis was the commonest subtype in the OH group, and systemic JIA was the commonest in the SRAH group. Half of the patients in the SRAH group had an active disease status at enrollment, which was higher than the OH group (50.0% vs. 21.1%, p = 0.066). More patients in the SRAH group had received orthopedic surgery due to JIA (25% vs. 3.5%, p = 0.034). Multiple logistic regression analysis showed that SRAH was independently related to systemic JIA (OR = 37.6, 95%CI 1.2-1210.5; p = 0.041). Conclusion The subtype of systemic JIA, with its characteristics of early disease onset and active disease status, was the essential factor that significantly impacted adult height.